Penerapan Metode Analytical Hierarchy Procces (Ahp) Untuk Pengangkatan Karyawan Tetap - Matias Julyus Fika Sirait (Cattleya Darmaya Fortuna, 2020)
Employees are a determinant of the success of a company, therefore employees have a very important role in determining the progress of the company, the determination of permanent employees at the company is sometimes done not objectively, the assessment is done subjectively with unclear parameters, so that the results of the assessment are detrimental to employees who have the ability well. The criteria for determining permanent employees are performance, discipline, loyalty, experience, psychological tests, peer assessment. The results of the assessment of employees who participated in the employee selection named Jenter were employees who were selected as permanent employees with a value of 0.50.